Detecting higher-level similarity patterns in programs - Basit, H.A. (2013)
ESEC/FSE'05 - Proceedings of the Joint 10th European Software Engineering Conference (ESEC) and 13th ACM SIGSOFT Symposium on the Foundations of Software Engineering (FSE-13)